Selecting venues for AMIA events and conferences: guiding ethical principles. (17th May 2022) - Lehmann, Christoph U; Fultz Hollis, Kate; Petersen, Carolyn; DeMuro, Paul R; Subbian, Vignesh; Koppel, Ross; Solomonides, Anthony E; Berner, Eta S; Pan, Eric C; Adler-Milstein, Julia; Goodman, Kenneth W
Abstract: A discussion and debate on the American Medical Informatics Association's (AMIA) Ethical, Legal, and Social Issues (ELSI) Working Group listserv in 2021 raised important issues related to a forthcoming conference in Texas. Texas had recently enacted a restrictive abortion law and restricted voting rights. Several AMIA members advocated for a boycott of the state and the scheduled conference. The discussion led the AMIA Board of Directors to request that the organization's Ethics Committee provide general guidance for principle-based venue selection. This document recommends overarching principles for the venue selection for future AMIA events and conferences. Discussions by the AMIA Board, the Ethics Committee, and the ELSI Working Group informed these recommendations, and this document on guiding principles was approved by the AMIA Board of Directors in April 2022.